Geochemical and thermodynamic factors of high-dispersed mineral formation in the fluidization zones - V.N. Trufanov, A.V. Trufanov, (Opción, 2019)
The study aims to investigate geochemical and thermodynamic factors of high-dispersed mineral formation in the fluidization zones via comparative qualitative research methods. As a result, when local cavitation anomalies with very high thermodynamic differences occur, the appearance of diamond nanocrystals seems quite probable in the process of opening of the releasable sources. In conclusion, the development of the reverse explosion effect, nanocrystals of non-ferrous, rare and noble metals may be formed, which form previously unknown associations of industrially significant sources of ore and non-metallic mineral matter.